The Effect of Ethnoscience-Based CTL (Contextual Teaching and Learning) Model on Motivation and Physics Learning Outcomes of Students on the topic of Sound Waves - Rizky Munandar; Putu Ayas Ditha Apsari; Muhammad Hendri Diarta; Nurhasanah Nurhasanah; Kurnia Julianti Arni; Solihin Rahmat; Zahratul Walihah; Hikmawati Hikmawati (Pascasarjana, Mataram University, 2023)
The purpose of this study was to determine the effect of using the ethnoscience-based CTL (contextual teaching and learning) model on student motivation and learning outcomes on the topic of sound waves in class XI MIPA 4 at SMA Negeri 2 Mataram. This research method uses a mixed method, with the sampling technique using the purposive sampling method. The research subjects were 26 students of class XI MIPA 4 SMA Negeri 2 Mataram. Quantitative data were analyzed using statistical analysis techniques through t-test by first doing normality test and homogeneity test. The results showed that the calculated t value was greater than the t table value, which was 9,203 which was greater than 2,068. Based on the results of the interviews showed an increase in the understanding of the concepts possessed by students. Thus, there is an effect of applying the Ethnoscience-based CTL model to students' motivation and learning outcomes